2023
DOI: 10.1002/mnfr.202200884
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effect of Clostridium butyricum‐Derived Extracellular Vesicles in Ulcerative Colitis: Impact on Host microRNAs Expressions and Gut Microbiome Profiles

Abstract: Score: Probiotics extracellular vesicles (EVs) have shown potential as EV-based nanomaterials therapy for the treatment of inflammatory bowel disease (IBD). Although probiotic Clostridium butyricum has been reported to be protective in various models of intestinal inflammation, the therapeutic effects of C. butyricum-derived extracellular vesicles (CbEVs) in IBD remain to be demonstrated. Methods and results: In this study, multi-omics sequencing is combined with an in vitro model of lipopolysaccharide-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“… 159 Cb -MVs restored the expression miR-199a-3p, which targets map3k4, thereby suppressing proinflammatory mitogen-activated protein kinase (MAPK) and NF-κB signaling pathways, ultimately contributing to Cb -MVs mediated anti-inflammatory effect. 154 Pretreatment with Akk -derived MVs in vitro mitigated the production of the proinflammatory cytokine IL-6 from colonic epithelial cells upon stimulation by pathogenic E. coli MVs. 150 Administration of MVs derived from Ec N to DSS-treated mice significantly reduced levels of proinflammatory cytokines IL-1β, TNF-α, and IL-17 in DSS-treated mice.…”
Section: Potential Therapeutic Applications Of Mvs In Ibdmentioning
confidence: 98%
See 4 more Smart Citations
“… 159 Cb -MVs restored the expression miR-199a-3p, which targets map3k4, thereby suppressing proinflammatory mitogen-activated protein kinase (MAPK) and NF-κB signaling pathways, ultimately contributing to Cb -MVs mediated anti-inflammatory effect. 154 Pretreatment with Akk -derived MVs in vitro mitigated the production of the proinflammatory cytokine IL-6 from colonic epithelial cells upon stimulation by pathogenic E. coli MVs. 150 Administration of MVs derived from Ec N to DSS-treated mice significantly reduced levels of proinflammatory cytokines IL-1β, TNF-α, and IL-17 in DSS-treated mice.…”
Section: Potential Therapeutic Applications Of Mvs In Ibdmentioning
confidence: 98%
“…Several studies have shown that miRNAs are significantly altered in colitis, and interaction of MVs with some of these miRNAs can either promote or reverse colitis in mice via different mechanisms. For instance, Cb -MVs restored miR-199a-3p expression, 154 treatment of MVs isolated from feces of colitis mice with miR-200b-3p rescued colitis in mice, 167 Fn -MVs facilitated downregulation of miR-574-5p expression exacerbating colitis. 134 These studies reveal that miRNAs could serve as potential targets for IBD diagnosis, progression, and therapy.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations